Generic strategies: a driver for firms competitiveness in Nigerian Fast Moving Consumers Goods (FMCGs) sector / Abayomi Olarewaju Adeoye, Sunday Stephen Ajemunigbohun and Olajide Idowu Okunbanjo - Adeoye, Abayomi Olarewaju; Ajemunigbohun, Sunday Stephen; Okunbanjo, Olajide Idowu (Faculty of Business and Management, 2023)
Competitiveness has become one of the objectives of firms in today's world especially in consumer goods sector. Every firm wants to have a reasonable share in the market to achieve specific firm goals which competitiveness is part of. To achieve this objective, consumers goods firms need to adopt appropriate strategies. Thus, the need to see how Porter generic strategies could drive competitiveness strength of Fast Moving Consumer Goods (FMCGs) in Nigeria. The study employed survey research design and primary source of data collection via questionnaire as well as multiple sampling techniques (simple and stratified). Simple regression was utilized as data analytical tool and it was found that differentiation and focus strategies have significant effect on FMCGs firms competitiveness. The study concluded that generic strategies (differentiation and focus) are determinants for firms competitiveness in FMCGs sector. It was therefore recommended that FMCGs firms should continue to deploy differentiation and focus strategies to achieve their competitive objectives.